2018
DOI: 10.5004/dwt.2018.22844
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth elements removal techniques from water/wastewater: a review

Abstract: a b s t r a c tThe rare-earth elements (REEs) remain very important due to the growing increase in their demand and for their critical and indispensable use in many high-tech industries today. This growing demand for REEs has led to an increased environmental exposure and water pollution from numerous REEs commercial products and as a result, the recovery of REEs is a significant issue that requires appropriate consideration. There are diverse and various strategic techniques available to remove metal ions fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 140 publications
0
30
0
Order By: Relevance
“…Among them, most methods are costly and require much energy consumption, are harmful to the environment, and are inefficient in processing low concentrations of rare earth elements [ 8 ]. Considering technology, the economy and environmental protection, the adsorption method was chosen as the method to remove rare-earth elements from pollutants [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, most methods are costly and require much energy consumption, are harmful to the environment, and are inefficient in processing low concentrations of rare earth elements [ 8 ]. Considering technology, the economy and environmental protection, the adsorption method was chosen as the method to remove rare-earth elements from pollutants [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ion-exchange consists of adsorbing REE ions from the leachates onto an exchanger that is specific and selective for REEs. In a reverse process, REE ions are desorbed from the exchanger during an elution step [94]. The ion-exchange method has been used for decades and is highly selective.…”
Section: Methods Of Ree Recoverymentioning
confidence: 99%
“…Another emerging method for REE separation and purification is solid-liquid extraction. This method uses nanoporous materials such as polymeric fibres, or silica and carbon based sorbents to separate and purify the REEs [94,96]. In a recent study by Hu et al [95], silica and carbon-based sorbents were reported for REE separation and purification.…”
Section: Methods Of Ree Recoverymentioning
confidence: 99%
“…The Supporting Information describes the procedures followed as well as the background information for adsorption models, kinetics, and thermodynamics. Since Table S1 shows that the pH for La 3+ and Ce 3+ in aqueous solutions is in the range 3–7 and the pH range of mining wastewater is 4.5–5.5, a pH of 5 was selected as an average representative value.…”
Section: Methodsmentioning
confidence: 99%